Analysis of the Quality of Used Cooking Oil Used in Frying Chicken - Dian I Sinurat; Ramlan Silaban (Universitas Negeri Medan, 2021)
This study aims to determine the quality of oil quality that is used repeatedly by frying chicken with the SNI. Bulk oil is used for frying the chicken with 11 frying repetitions. Repetition of oil before frying, repeat 1 time frying up to 10 frying times. Then the oil is tested for water content, Free Fatty Acid (FFA), peroxide value and iodine value. From this study, the quality of cooking oil was obtained for the range of: water content 0.03- 1.04%(w/w), Free Fatty Acids (FFA) 0.39-1.01%(w/w), peroxide value 5,99-18,465 mekO2/kg, iodine value 3.255-3.55 gI2/100g oil. Based on the various tests, the water content up to the oil from frying 3, Free Fatty Acid to oil from frying 3, the peroxide value to frying oil 4 still meets the SNI 01-3741-2013 oil quality standard. And in the iodine value test, all repeated frying results still meet the SNI 01-3741-2013 oil quality standard.